Representation of Ideology in Local Wisdom Verbal Forms: The Discourse Analysis of Islamic Friday Sermon - Sukirman, Sukirman; Salam, Salam; Aswar, Nurul; Firman, Firman; Mirnawati, Mirnawati; Rusdiansyah, Rusdiansyah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2022)
This study aims to reveal the ideology represented by the preachers through Friday sermons expressed in the form of local wisdom in Palopo City. This study used a qualitative approach to describe and to interpret research data. The data generated from words, phrases, and sentences contain social and religious ideology for data acquisition used a recording instrument. The data source was obtained from the preacher's narrative through expressions of local wisdom. Furthermore, the data were analyzed using the techniques of description, interpretation and explanation. The results showed that the narrative of ideology combined with the expression of local wisdom in the Friday sermon formed the competence of reasoning power and attractiveness of the congregation. It motivates, influences, and encourages worshipers to engage in increasing pious social behavior. Thus, the essence of the sermon's purpose, which states the invitation, has been realized in the practice of diversity (social and religious). الملخص لملخص: تهدف هذه الدراسة إلى الكشف عن الفكر الذي نقله الخطباء في خطبة الجمعة المعبر عنه في شكل الثقافة المحلية التي جرت في مدينة بالوبو. في هذه الدراسة، تستخدام المنهج النوعي لوصف وتفسير بيانات البحث. مصدر البيانات مأخوذ من تعبير الخطباء المعبر عن الثقافة المحلية. تحتوي البيانات من الكلمات والعبارات والجمل الفكرية الدينية الإجتماعية. للحصول البيانات، تستخدام أداة تسجيل . ثم تحلل البيانات باستخدام تقنيات الوصف والتفسير والشرح. وقد وجد أن سرد الفكر المتكامل مع تعبير الثقافة المحلية في خطبة الجمعة يمكن أن يحفز قوة التفكير وجاذبية المصلين. هذا يحفز المصلين ويؤثر عليهم ويشجعهم على عمل وإرتقاء التقوى الإجتماعية. وهكذا ، فإن جوهر الغرض من الخطبة هو الدعوة وقد تحقق في ممارسة التنوع (التقوى الإجتماعية). الكلمات المفتاحية: التمثيل الأيديولوجي. حكمة محلية؛ شكل لفظي خطبة الجمعة Abstrak Penelitian ini bertujuan mengungkap ideologi yang direpresentasikan para khatib melalui khutbah jumat yang diekspresikan dalam bentuk kearifan lokal yang berlangsung di Kota Palopo. Dalam penelitian ini digunakan pendekatan kualitatif mendeskripsikan dan menginterpretasi data penelitian. Sumber data diperoleh dari penuturan khatib berupa ungkapan kearifan lokal. Data dihasilkan dalam bentuk kata, frasa dan kalimat mengandung ideologi religius sosial. Untuk perolehan data digunakan instrumen perekam. Selanjutnya, data dianalisis dengan teknik deskripsi, interpretasi, dan eksplanasi. Ditemukan bahwa penuturan ideologi yang dipadu dengan ungkapan kearifan lokal dalam khutbah jumat membentuk kompetensi daya nalar dan daya tarik jamaah. Hal tersebut memotivasi, mempengaruhi dan mendorong jamaah melakukan perilaku kesalehan sosial yang semakin meningkat. Dengan demikian, hakikat tujuan khutbah yang menyatakan ajakan telah diwujudkan dalam pengamalan keberagaman (religius sosial). Kata Kunci: Representasi ideologi; Kearifan lokal; Bentuk verbal; Khutbah jumat